Neuroprotective effects of carvacrol against Alzheimer's disease and other neurodegenerative diseases: A review - Zahra Azizi; Nahid Majlessi; Samira Choopani; Nasser Naghdi (Mashhad University of Medical Sciences, 2022)
Objective: Neurodegenerative diseases are considered an important cause of cognitive deficit and morbidity in old ages. Alzheimer's disease (AD) is one of these disorders affecting about 40 million people in the world at the present time. Available drug therapy is mostly symptomatic and does not modify or stop disease progression. Recently, biologically active chemicals from herbs have been studied to develop new therapeutic drugs. Carvacrol has shown positive properties on many neurological diseases. This compound is expected to have the ability to affect AD pathogenesis and therefore, it is considered an anti-AD agent.Materials and Methods: This review was conducted using PubMed, Google Scholar and Science Direct bibliographic databases until November 2021. For data collection, the following keywords were used: carvacrol, neuroprotective, cognition, anti-inflammatory, antioxidant, Acetylcolinesterase inhibitor (AChEI), Alzheimer's, Parkinson's, epilepsy, stroke, ischemic brain injury, and neurodegenerative diseases.Results: This review summarizes in vitro and in vivo studies on protective potential of carvacrol in neurodegenerative disorders and various underlying mechanisms, such as anti-inflammatory, antioxidant, and anticholinesterase effects. Conclusion: We gave an overview of available literature concerning neuroprotective effects of carvacrol in ameliorating the neurodegenerative diseases symptoms in vivo and in vitro. Particular attention is given to AD. Several neuro-pharmacological actions of carvacrol have been summarized in the current review article including anti-inflammatory, antioxidant, and AChEI properties.